Enhancing River Water Quality: A Collaborative Effort Between BrantaSae, RIVER, and Citizen Science for Sustainable River Cleaning - Siti Nurjanah; Ahmad Rizal; Rina Setiawati (Journal of Community Action, 2026)
River water pollution is a significant environmental issue affecting aquatic ecosystems and human health. In this study, we explore the collaborative efforts between BrantaSae, RIVER, and citizen science initiatives to enhance river water quality through sustainable cleaning practices. The partnership aims to integrate technology, community participation, and scientific research to address river pollution effectively. BrantaSae's innovative monitoring tools, combined with RIVER's research framework, have enabled real-time data collection on water quality. Citizen science, as an inclusive approach, engages local communities in data collection, fostering awareness and encouraging direct involvement in river cleaning activities. The collaboration has demonstrated promising results in improving water quality, reducing pollutants, and enhancing community engagement in river conservation. The study emphasizes the importance of multi-stakeholder collaboration and the role of citizen science in promoting sustainable environmental practices. By combining scientific knowledge with community-driven efforts, this initiative serves as a model for future river management strategies aimed at preserving water quality and biodiversity for future generations.